SolidarIta: a Fundraising System to Support Organized Civil Society Institutions - Almeida, Natália M. T. de; Silva, Milady R. A. da; Batista, Bruno G. (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2025: Anais do XXI Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2025.245953, 2025)
Context: In contexts of economic vulnerability, non-profit and solidarity organizations, such as Organized Civil Societies (OCSs) in Brazil, play a pivotal role in promoting equity and combating inequalities. With approximately 879,000 OCSs in 2023, these entities act where the State and the market fail, but face challenges in raising funds due to a still limited donation culture. Problem: Transparency and integrity in fundraising are essential, but money laundering and threats such as extortion and phishing compromise transaction security. The lack of clarity in operations can undermine donors’ trust, making fundraising even more difficult. Solution: This paper presents a solution using Information Technology through the SolidarIta system, which aims to simplify the donation process for needy entities. IS Theory: SolidarIta allows registered organizations to create wish lists, facilitating the digital connection between donors and suppliers, such as supermarkets. Donors can choose items and make payments, while partners care for delivery, ensuring transparency. Method: The investigative research used literature analysis to model the system, followed by data collection through questionnaires to assess its impact and usability. Summary of Results: The system has demonstrated its effectiveness, with 89.3% of participants expressing satisfaction and 93.6% finding it useful. These results instill confidence in the potential of the SolidarIta system. Contributions and Impact in the IS area: SolidarIta facilitates interaction between donors, organizations, and partners, promoting transparent and efficient donations, improving the user experience, and increasing engagement in solidarity actions.